HIV-1 drug resistance at virological failure versus immunological failure among patients failing first-line antiretroviral therapy in a resource-limited setting - S. Sungkanuparph (2018)
Antiretroviral treatment failure has been defined by immunological failure (IF) in some resource-limited settings whereas defining by virological failure (VF) has been widely used in developed countries. There is limited comparison of the levels of HIV-1 drug resistance between using VF and IF for the diagnosis of treatment failure. A retrospective cohort study was conducted among HIV-1-infected patients failing first-line antiretroviral therapy (ART). Of 95 patients, median CD4 and HIV-1 RNA were 158 cells/mm3 and 10,200 copies/mL, respectively. Patients in the IF group had higher HIV-1 RNA than those in VF group (23,820 versus 9510 copies/mL, P 1/4 0.008). Nucleoside reverse transcriptase inhibitor (NRTI)-, non-NRTI- and protease inhibitor-resistance-associated mutations (RAMs) were observed in 57.9%, 94.7% and 5.3%, respectively. Q151M, a multidrug RAM, was more commonly observed in the IF group (14.8% versus 2.9%, P 1/4 0.032). Using IF to diagnose treatment failure is associated with higher HIV-1 RNA levels and a higher rate of Q151M, which can limit the options for second-line ART.